‘Membangun Bali’; Strategi Menuju Arsitektur Bali yang Berkelanjutan - Bharuna S, Anak Agung Gde Djaja; Aritama, Anak Agung Ngurah; Mudra, I Ketut (Jurnal Arsitektur Universitas Udayana, 2025)
In Bali, the society is very harmonious, its traditional entity combines material and spiritual happiness. Almost all daily activities are carried out in a container with symbolic magic and are full of natural and cultural meaning. Likewise with traditional Balinese architecture, it has long been known that image and function represent the balance of God, humans and nature. As time goes by, society experiences changes, development brings the consequence that one party becomes more prosperous and intelligent, but on the other hand, people begin to experience changes in thinking. The concept of cultural tourism is increasingly widespread, it is suspected that cross-cultural events are occurring which are becoming more complicated to trace, and in the end the Balinese people are experiencing a dilemmatic conflict, religious life and culture are starting to be hit by secularism and materialism. The world of post-traditional Balinese architecture is experiencing various changes. There is architectural pluralism from modernism to postmodernism which is a reflection of the transitional state of society and its culture. What is disturbing is that architecture is not capable of forming a complete human being, instead it provides justification for such a cultural situation. Balinese society and architecture require a social contract to 'build Bali' that is new, and is able to provide a balance between culture, tradition and demands in a positive and sustainable manner. This study will provide a description of the state of architecture during the transition period and at the same time provide a sustainable strategy for the development of Balinese architecture in the present and future. Keywords: Balinese architecture, building Bali, sustainability strategy, tradition, culture